2017
DOI: 10.1021/jacs.7b08558
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Solvation Dynamics and Vibrational Coherences of Halogenated Boron-Dipyrromethene Derivatives Revealed through Two-Dimensional Electronic Spectroscopy

Abstract: Boron-dipyrromethene (BODIPY) chromophores have a wide range of applications, spanning areas from biological imaging to solar energy conversion. Understanding the ultrafast dynamics of electronically excited BODIPY chromophores could lead to further advances in these areas. In this work, we characterize and compare the ultrafast dynamics of halogenated BODIPY chromophores through applying two-dimensional electronic spectroscopy (2DES). Through our studies, we demonstrate a new data analysis procedure for extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 108 publications
4
47
0
Order By: Relevance
“…The values found for the MeOH solutions are in reasonably good agreement with recent measurements on a molecule with a similar structure. 30 These time constants are very fast and, especially in the case of PHDB, close to the time resolution of the experiment, leading to a non-negligible uncertainty in their determination. Nevertheless, beyond the exact value of time constants, the comparison of the decays recorded for different sample solutions reveals trends as a function of solvent and presence of the nitro group.…”
mentioning
confidence: 95%
“…The values found for the MeOH solutions are in reasonably good agreement with recent measurements on a molecule with a similar structure. 30 These time constants are very fast and, especially in the case of PHDB, close to the time resolution of the experiment, leading to a non-negligible uncertainty in their determination. Nevertheless, beyond the exact value of time constants, the comparison of the decays recorded for different sample solutions reveals trends as a function of solvent and presence of the nitro group.…”
mentioning
confidence: 95%
“…Thus, using spectrally‐resolved pump‐probe technique, one can also envisage the idea of directly monitoring the time‐dependent gain in stimulated emission spectrum obviating the need of spectral reconstruction and estimation of time‐zero spectrum in non‐polar solvent, which we present in this work. It is worthy to mention here that spectrally‐resolved pump‐probe spectroscopy has been used to study synergistic behaviour in binary solvent mixtures and vibrational wavepacket interferometery measuring solvation in methanol and in proteins; two dimensional electronic spectroscopy has also been used to study solvation . Fluorescence correlation spectroscopy and time‐dependent Stokes shift was also implemented to study solvation dynamics in membranes .…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to mention here that spectrally-resolved pump-probe spectroscopy has been used to study synergistic behaviour in binary solvent mixtures [31] and vibrational wavepacket interferometery measuring solvation in methanol and in proteins; [32] two dimensional electronic spectroscopy has also been used to study solvation. [33,34] Fluorescence correlation spectroscopy and timedependent Stokes shift was also implemented to study solvation dynamics in membranes. [35] As discussed in the following section, extending our preliminary work [36] here we present experimental results which focuses on establishing a general method of studying solvation dynamics by spectrallyresolved degenerate pump-probe spectroscopy with a particular emphasis on estimating early time solvation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the 2DES technique to vibrational coherence dynamics also allowed the identification of a possible relaxation mechanism involving specific interaction between vibrational modes of the dye and the solvent. Also Lee and co-workers studied different BODIPY, i.e., BODIPY-2H and BODIPY-2I chromophores dissolved in methanol by applying 2DES [56]. The authors observed that after electronic excitation, the BODIPY molecules relax in response to the change in the charge distribution, through solvent reorganization and/or intra-and intermolecular vibrational energy redistribution.…”
Section: Recent Advances In Multidimensional Ultrafast Spectroscopy Amentioning
confidence: 99%
“…The authors observed ultrafast solvation dynamics of the two dyes on a sub-100 fs time scales. Furthermore, they demonstrated a new data analysis procedure for extracting the dynamic Stokes shift from 2DES spectra, focusing on monitoring the frequency changes associated with the SE, revealing an ultrafast solvent relaxation [56].…”
Section: Recent Advances In Multidimensional Ultrafast Spectroscopy Amentioning
confidence: 99%